2015
DOI: 10.1007/s10508-014-0452-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gender Nonconformity in Flanders, Belgium

Abstract: Gender nonconformity refers to the extent to which a person's gender identity, gender role and/or gender expression differs from the cultural norms prescribed for people of a particular sex, within a certain society and era. Most data on gender nonconformity focus on the prevalence of gender dysphoria (which also includes a distress factor) or on the number of legal sex changes. However, not every gender nonconforming individual experiences distress or applies for treatment. Population-based research on the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(97 citation statements)
references
References 16 publications
7
87
1
2
Order By: Relevance
“…There is also a significant increase in people who self-diagnose as suffering from gender dysphoria and gender incongruence (Kuyper & Wijsen, 2014;Van Caenegem et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a significant increase in people who self-diagnose as suffering from gender dysphoria and gender incongruence (Kuyper & Wijsen, 2014;Van Caenegem et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Kuyper & Wijsen (2014) examined self-reported gender identity and dysphoria in a large Dutch population sample (N ¼ 8064, aged 15-70 years old), and found that 4.6% of people assigned male at birth and 3.2% of people assigned female at birth reported an 'ambivalent gender identity' (defined as equal identification with the other sex as with the sex assigned to them at birth) and 1.1% of people assigned male at birth and 0.8% of people assigned female at birth reported an 'incongruent gender identity' (defined as stronger identification with the other sex as with the sex assigned to them at birth). Recently, Van Caenegem et al (2015) reported results based on two population-based surveys, one of 1832 Flemish individuals and one of 2472 sexual minority individuals in Flanders, Belgium, examining the prevalence of 'gender incongruence' (defined as identifying stronger with the other sex than with the sex assigned at birth) and 'gender ambivalence' (defined as identifying equally with the other sex as with the sex assigned at birth). Their findings showed that the prevalence of 'gender ambivalence' or non-binary gender was 1.8% in natal men and 4.1% in natal women.…”
Section: Prevalence Of Non-binary Peoplementioning
confidence: 99%
“…ASD has a prevalence of 20.6:10,000 with a male to female ratio of 4.2 to 1 [14], although a recent report has suggested that rates may be as high as 1 in 50 for males and 1 in 150 for females [15].…”
Section: Introductionmentioning
confidence: 99%
“…Population studies suggest a significantly higher prevalence despite the fact that it remains unknown how many people who identify as trans go on to seek cross-sex hormone treatment and/or gender-related surgery [3,4]. Research has already reported high levels of mental health problems, particularly depression and non-suicidal self-injury (NSSI), among the trans population [5,6,7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%